Research Status of Microwave-assisted Reduction Technology of Pyrolusite - Qiannan, Li; Yeqing, Ling; Hewen, Zheng; Zhi, Yang (Current Microwave Chemistry, 2021)
Manganese ore is an important metallurgical raw material that holds an important strategic position in the national economy of China. However, the grade of manganese ore in the country is mostly low, and the utilization efficiency of low-grade manganese ore resources is low, which seriously restricts the healthy and stable development of China’s metallurgical industry. As a new green heating method, microwave is expected to address the problems of conventional methods and realize the effective utilization of low-grade manganese ore. In this paper, the research status of the microwave composite reduction of pyrolusite in recent years is reviewed. Microwave plays an important role in metallurgy, and it is the current direction pursued to improve the research level of microwave heating and extend it to actual industrial processes.
Keywords: manganese ore